Impact of Industry 4.0 on Supply Chain Management: An Application in the Dairy SectorImpact of Industry 4.0 on Supply Chain Management: An Application in the Dairy Sector - Hameedu Rawther, Nijas Pampadiyil (Digital Repository of Theses - SSBM Geneva, 2025)
Industry 4.0 is the fourth industrial revolution that integrates advanced technologies into industrial and manufacturing processes to enhance efficiency, improve decision-making, and bring automation to processes. This research has been carried out to conduct a crosscomparison of the application of different Industry 4.0 technologies in the supply chain of the dairy industry in India and the Kingdom of Saudi Arabia (KSA). The research has been qualitative and conducted using interviews of the relevant personnel in the dairy industry of both countries. The sample size of the study consisted of 19 respondents: 10 respondents from India and 9 from the KSA dairy industry. The results of structured interviews have been analyzed using the thematic analysis technique. The results of the thematic analysis helped generate four main themes and certain subthemes under each category. In this regard, the main themes of the study included Industry 4.0 technologies used in the supply chain of the dairy sector, benefits of implementing Industry 4.0 technologies in the supply chain of the dairy sector, challenges of implementing Industry 4.0 in the supply chain of the dairy sector, and resilience brought by Industry 4.0 in the dairy sector supply chain. A further investigation has shown that the main Industry 4.0 technologies used in the dairy industry supply chain consisted of Big Data, Internet of Things (IoT), RFIDs, Artificial Intelligence (AI), Machine Learning, Cloud Computing, Augmented Reality, Cyber Physical Systems, 3D Printing, and Robotics. The results have indicated that the application of these technologies is more prevalent in the Saudi dairy sector while Indian dairy is lagging. However, the main challenges included a lack of resources, inconsistent infrastructure, a shortage of skilled personnel, and others. Those who have implemented these technologies effectively reported smooth information sharing, real-time monitoring, timely response to disruptions, and an integrative environment which all lead to greater resilience. The cross-comparison of the two countries shows KSA leading ahead of India in the application of I4.0 technologies in the dairy industry, however, the application is limited in KSA as well. The results of the study have added to existing literature on I4.0 in Dairy Industry while it also provides important implications for policymakers to enhance application of I4.0 to avail full potential of these technologies in dairy industry.